LANGUAGE POLICY IN BILINGUAL FAMILIES IN LANGSA - Alfi Sahri; Fadlia Fadlia; Makhroji Makhroji; Imran Imran; Evi Zulida (Journal of Education, Linguistics, Literature and Language Teaching, 2019)
The purpose of this research are: To find out how do parents in bilingual families decide language policy in their family and to find out what are factors influencing of deciding language policy. This study uses descriptive qualitative methods. The subjects of this study were two-language families in the birem puntong with twenty-five families as subjects. The research instruments were dept interview, recording equipment and documentation. The results of these research were birem puntong group did not have a policy to maintain and use regional language at home and in the environment. And factors that influence the use of the term language policy in bilingual are, parental language use and ideology and children and language practice.